The Effect of Environmental, Social, and Governance (ESG) Disclosure on Investment Efficiency (an Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Amarta, Ni Wayan Della; Hendrawaty, Ernie (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. As ESG practices gain global prominence, their role in enhancing transparency and reducing information asymmetry is considered crucial for sustainable business and efficient investment decisions. Using a purposive sampling method, 37 manufacturing firms were analyzed over a five-year period, employing secondary data from international ESG databases. Panel data regression with the Random Effect Model was used to test both aggregated and disaggregated ESG dimensions—environmental, social, and governance—against investment efficiency, measured through residuals of the Biddle et al. (2009) investment model. The findings indicate that aggregated ESG disclosure does not significantly influence investment efficiency. However, when disaggregated, social disclosure demonstrates a significant positive effect, while governance disclosure shows a significant negative effect. Environmental disclosure was found to have no significant impact. These results suggest that while social responsibility initiatives contribute positively to investment decision-making by improving stakeholder trust and reducing agency conflict, overly rigid governance mechanisms may limit managerial flexibility, hindering efficient investment. The study highlights the limited awareness and implementation of ESG practices in Indonesia’s manufacturing sector, as well as the need for future research to explore mediating factors or expand samples across other sectors or countries. The research contributes to understanding ESG’s nuanced role in shaping financial performance within emerging markets.